Changes to household practices pre- and post-occupancy in an Australian low-carbon development - Breadsell, Jessica; Morrison, Greg (ELSEVIER, 2020)
Limiting study to a narrow range of energy and water using activities is insufficient to provide a holistic understanding of household resource flows. Consideration of a wide range of social practices is needed. With the rise of low-carbon developments featuring energy or water efficient technology and design around the world, the way residents interact with the design and technology and community is vital to understanding if these households and developments will meet their intended design goals. The opportunity to study resident's pre-and post-occupancy resource consumption is a unique opportunity to examine how design, technology and community influence household practices. This article studied 13 Australian household's practices of waste management, food shopping, item purchasing, travel and laundry practices for two weeks before and after moving into a low-carbon development, while the home system of practice is in a stable phase. This provides an opportunity to comment on the state of interlocking of resident's home system, from lightly interlocked to highly. Post-occupancy, the presence of solar panels influenced when some residents put the washing machine and tumble drier on, however only when the resident was home. Many residents are conscious of putting these on during the day or use timers where they had not previously. Changes to resident's travel practices were not as broad as they anticipated before the move, while recycling rates increased, influenced by a supportive community and shopping practices became more localised through the use of smaller food retailers. Results show that resident's resource use is heavily influenced by their work and socialising routines, which are not commonly focused on when attempting to change household resource use behaviours. A traditional focus on psychological approaches targeting values and attitudes fails to adequately address these factors, whereby a social practice theory approach allows for their consideration in influencing resource use in the home.